Attitude of Higher Institution Students towards the Use of Family Planning Methods and Cohabitation in Ondo State, Nigeria - Fatuyi, A; Gbore, L. O.; Tosin .E. Akinduyo; Adenodi, D.O.; N.P.M. Mabaso (CV. AFDIFAL MAJU BERKAH, 2024)
This study investigated higher institution students' attitudes toward family planning methods and cohabitation in Ondo State, Nigeria. This study used a descriptive survey research design and a sample of 560 higher institution students selected through a multi-stage sampling procedure from the seven higher institutions in Ondo State, Nigeria. The instrument used for data collection was a structured questionnaire with two sub-scales titled ‘Students’ attitudes towards contraceptive use inventory’ and ‘Attitudes towards cohabitation questionnaire’ The data collected were analyzed using frequency count, percentage and correlation analysis. The study results showed a high prevalence of cohabitation among higher institution students in Ondo State with 408 (72.86%) of the 560 respondents engaging in cohabitation. Also, significant relationships existed between attitudes towards the use of family planning methods and cohabitation among higher institution students (r= 0.479, P< 0.05). Based on the findings, it was concluded that a highly prevalent level of cohabitation exists among students of higher institutions and a positive relationship existed between the use of family planning methods and cohabitation among the students. Therefore, it was recommended that the government and management team of each of the higher institutions should provide, within the campus, enough affordable accommodation and rules guiding visitation to opposite-sex hostels.